Implementation of Problem Solving Method To Improve Student's Critical Thinking In Islamic Religious Education Learning - Hanafiah Hanafiah; Annisa Shivia Fauziyah; Deden Badrussalam (Universitas Muhammadiyah Enrekang, 2023)
In the learning process students often ask about how something works or why certain things happen as they do or even tend to have good problem solving skills. They are people who carefully analyze individual or group problems. Children's ability to solve problems (Problem Solving) can improve cognitive abilities both in thinking and creativity. problem solving to be able to improve students' cognitive abilities or critical thinking skills of students at Surya Kencana Bhakti Middle School. This study uses a type of qualitative research. Qualitative research is a type of research that produces findings that cannot be achieved by using statistical procedures or by other means of quantification. The importance of critical thinking and problem solving in PAI learning is so that students can stimulate, analyze, and synthesize exactly where the problem is, on their own initiative. In PAI students are required to have the ability to see causation or relationships from various information obtained so that they can find the key to solving problems.